2008
DOI: 10.1186/1477-7819-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen-rich clear cell carcinoma of the breast

Abstract: Background: Glycogen-rich carcinoma of the breast is a rare histological subtype of breast cancer, usually reported to have poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 10 publications
2
38
0
1
Order By: Relevance
“…The patient is well today and has had no clinical recurrence of the disease after 2.5 years of follow-up without radiotherapy or chemotherapy. Markopoulos et al 13 recently reported a patient with GRCC who was free of the disease 48 months after surgery. The prognosis is probably better if the tumor is detected early and if there are no lymph node metastases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The patient is well today and has had no clinical recurrence of the disease after 2.5 years of follow-up without radiotherapy or chemotherapy. Markopoulos et al 13 recently reported a patient with GRCC who was free of the disease 48 months after surgery. The prognosis is probably better if the tumor is detected early and if there are no lymph node metastases.…”
Section: Discussionmentioning
confidence: 97%
“…Some investigators have reported that mammography revealed a malignant mass with an irregular margin and spicula formation with fi ne calcifi cation. [8][9][10][11][12] Markopoulos et al 13 reported that mammography disclosed a 3.5-cm lobulated, circumscribed mass with no evidence of malignancy, which suggested a fi broadenoma. In this study, mammography could not identify the tumor behind the dense breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are insufficient published data about the imaging characteristics of GRCCC [12,17]. The mammogram may be inconclusive due to dense breast tissue [17], and the tumor may have benign characteristics on mammography [18]. Some authors have suggested that GRCCC is associated with an aggressive clinical course [2,3] compared to conventional ductal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that GRCCC is associated with an aggressive clinical course [2,3] compared to conventional ductal carcinoma. The clinical course of patients with GRCCC may vary depending on histological characteristics such as low grade and positive ER expression [18]. Further studies are however needed to better determine the behavior and prognosis of GRCCC [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor characteristics of invasive cancer associated with PD are more aggressive than those of invasive cancer not associated with PD. GRCCC of the breast is a rare sub¬type of invasive duc- tal carcinoma and generally tends to follow an aggressive clinical course (11,12).…”
Section: Case Reportmentioning
confidence: 99%